Patients' preferences and health utility assessment with SF‐6D and EQ‐5D in patients with chronic hepatitis C treated with sofosbuvir regimens. Issue 6 (15th July 2014) - Stepanova, M.; Nader, F.; Cure, S.; Bourhis, F.; Hunt, S.; Younossi, Z. M.
Summary Background Health utilities measure patients' preferences for a health state. Aim To assess health utilities for sofosbuvir‐containing therapy for chronic hepatitis C. Methods The SF‐6D utility scores were derived from the SF‐36 instrument administered at baseline, during and post‐treatment to participants of the previously reported clinical trials of sofosbuvir. EQ‐5D utility scores were also approximated from the SF‐36 using a regression model. Results Nine hundred and ninety‐four patients were enrolled. Baseline SF‐6D and EQ‐5D scores were 0.66 ± 0.13 and 0.71 ± 0.22, respectively (the POSITRON trial), 0.71 ± 0.16 and 0.76 ± 0.23 (FISSION), 0.70 ± 0.14 and 0.75 ± 0.22 (FUSION), 0.72 ± 0.15 and 0.79 ± 0.22 (NEUTRINO). In all studies, SF‐6D and EQ‐5D scores were highly correlated with each other. (r = 0.83–0.87, P < 0.0001). After 12 weeks, patients receiving sofosbuvir + ribavirin (POSITRON) had similar utility scores to placebo (P > 0.05). Patients receiving 12 and 16 weeks of sofosbuvir + ribavirin (FUSION) had similar utility scores (P > 0.05). In FISSION, patients receiving sofosbuvir + ribavirin had significantly better utilities compared to patients receiving interferon + ribavirin (P < 0.001). Patients receiving sofosbuvir + ribavirin + interferon (NEUTRINO) had a decrease in utilities during treatment (SF‐6D: from 0.72 to 0.62, EQ‐5D: 0.79 to 0.65; P < 0.0001) similar to that observed in patients receiving pegylated interferon + ribavirin for 24 weeks in FISSION (0.72 to 0.62 and 0.77 to 0.65, respectively, P < 0.0001). After 12 weeks post‐treatment, patients with SVR (FUSION) had improvement in SF‐6D (+0.026 from baseline, P = 0.013) and EQ‐5D (+0.043, P = 0.013). In multivariate analyses, baseline depression, anxiety, fatigue, insomnia and treatment‐related anaemia were the most consistent predictors of utilities. Conclusions Patients' health utilities are minimally impacted by sofosbuvir + ribavirin treatment, as compared to interferon‐based, therapy regardless of treatment duration. Clinical trials' numbers: NCT01542788 (POSITRON), NCT01497366 (FISSION), NCT01604850 (FUSION), NCT01641640 (NEUTRINO).